2007
DOI: 10.1016/j.jasms.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Improved sequencing of oxidized cysteine and methionine containing peptides using electron transfer dissociation

Abstract: Oxidative modifications to the side chains of sulfur-containing amino acids often limit the number of product ions formed during collision-induced dissociation (CID) and thus make it difficult to obtain sequence information for oxidized peptides. In this work, we demonstrate that electron-transfer dissociation (ETD) can be used to improve the sequence information obtained from peptides with oxidized cysteine and methionine residues. In contrast to CID, ETD is found to be much less sensitive to the side-chain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 51 publications
1
51
1
1
Order By: Relevance
“…The Combo SIC for a given fragment ion can be viewed as the peptide level MS1 SIC (denoted by the first term in equation (1)) fractionated according to the corresponding tandem ion intensity (denoted by second term in equation (1)). The signals in the uncorrected S 2ij (t) plots are susceptible to fragmentation variation as a function of the side chain oxidation chemistry (35,36). The combination of the MS1 and MS2 level information as in equation (1) helps to minimize such bias.…”
Section: Combo Sics-mentioning
confidence: 99%
See 2 more Smart Citations
“…The Combo SIC for a given fragment ion can be viewed as the peptide level MS1 SIC (denoted by the first term in equation (1)) fractionated according to the corresponding tandem ion intensity (denoted by second term in equation (1)). The signals in the uncorrected S 2ij (t) plots are susceptible to fragmentation variation as a function of the side chain oxidation chemistry (35,36). The combination of the MS1 and MS2 level information as in equation (1) helps to minimize such bias.…”
Section: Combo Sics-mentioning
confidence: 99%
“…The tandem MS signals can be affected by the variation in fragmentation as a function of the side chain oxidation chemistry (35,36). A combination of signals from both MS1 and MS2 levels in the form of Combo plots helps to minimize such bias.…”
Section: Estimating Extent Of Oxidation For Individual Fragment Ions mentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry has become the principal tool for the identification of peptides and proteins, and several recent studies have been concerned with the fragmentation behavior of protonated peptides containing oxidized cysteine residues [15][16][17][18][19][20][21]. For peptides in which the ionizing protons are sequestered at highly basic arginine side chains effectively fixing the charge, i.e., non-mobile proton conditions, cleavage of the amide bond C-terminal to cysteic acid residues affords abundant y, d, or b-H 2 SO 4 ions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The facile nature of this fragmentation may reduce sequence coverage as it outcompetes other low energy CID pathways. Vachet and co-workers have demonstrated that electron transfer dissociation is comparatively insensitive to the presence of a cysteine suflinic acid and so provides greater sequence coverage than CID for cysteic acid containing peptides [21].…”
Section: Introductionmentioning
confidence: 99%